Perjuangan Seorang Ibu dalam Puisi Kukusan Karya Emi Suy dan Puisi Bunda Airmata Karya MH Ainun Najib: Kajian Sastra Bandingan - Maulida Laily Kusuma Wati; Teguh Supriyanto; Agus Nuryatin (SULUK : Jurnal Bahasa, Sastra, dan Budaya, 2024)
This research aims to determine the relationship between the poem Kukusan by Emi Suy and the poem Bunda Airmata by MH Ainun Najib. The theory used in this research uses comparative literary theory which discusses metaphor, symbols and relevance in the two poems. The data collection technique uses first level semiotic reading, namely heuristics. The data analysis technique uses the second level of semiotic reading, namely hermeneutics. The results of the analysis of the poem "Bunda Airmata" by M.H. Ainun Najib and "Kukusan" by Emi Suy are that they both raise the theme of a mother's struggle, although through different writing styles, context and symbolism. In "Our Lady of Tears," the mother is described as a figure who has a deep spiritual dimension, guides her children in religious values, and is able to convey emotional strength through her tears. On the other hand, "Steamed" depicts the mother as a figure who faces struggles like the bamboo steaming process, reflecting resilience and strength in facing the pressures and difficulties of life.